The Logical Relationship between Facts and Values - Samhouri, Maha (Jordan Journal of Social Sciences, 2020)
Through using a logical analysis methodology, this paper tries to prove that we can only perceive facts through values as there are no facts that are devoid of any value. When the truth is explored herein, it is supposed that real issues are those that may be judged to be either true or false as perceived in the outer or real world. This entails that there is a value judgment on how realistic objective facts and, to this end, facts are collected to support assumptive values. Given that human is a rationale being, the first pillar for rationality is reasoning. Hence, when we commit an act or want to do “what is ought to be done” under certain circumstances, our act will be judged by the reasons and logical inference to do what is appropriate or correct. In other words, we act as such for rational reasons. Resercher provide assurances that we cannot separate realities or facts from values as any scientific undertaking or moral realization in a certain subject is directed by value-based attributes that include coherence or a state of no contradictions.